(untitled) (Nativa, 2020)
Atualmente, dados de sensoriamento remoto, como os do Tropical Rainfall Measuring Mission (TRMM), vem sendo utilizados para monitorar a distribuição da chuva no tempo e no espaço. O objetivo deste trabalho foi avaliar a qualidade dos dados da precipitação pluvial estimada pelo produto 3B43-TRMM no estado de Sergipe, nas escalas mensal e anual, entre 1998 e 2013. Os valores pontuais estimados pelo TRMM foram comparados com os dados de precipitação obtidos em 13 postos pluviométricos da Agência Nacional de Águas (ANA). Os indicativos estatísticos considerados foram o coeficiente de determinação (R²), erro médio absoluto (EMA), raiz do erro quadrado médio (REQM) e índice de concordância de Willmott (d). Os valores de R² foram de 0,49 e 0,16 nas escalas mensal e anual, respectivamente. Para a escala de tempo mensal as melhores estimativas do produto TRMM foram encontradas na região Semiárida do estado de Sergipe, com valores de R², EMA, REQM e d iguais a 0,54, 27,18 mm e 38,71 mm e 0,83, respectivamente. Palavras-chave: 3B43-TRMM; climatologia; hidrologia; chuva. ANALYSIS OF ESTIMATED PRECIPITATION DATA BY REMOTE SENSING IN THE SERGIPE STATE ABSTRACT: Currently, remote sensing data, such as that of the Tropical Rainfall Measuring Mission (TRMM), has been used to monitor the distribution of rain over time and space. The objective of this work was to evaluate the quality of the rainfall data estimated by the product 3B43-TRMM in the state of Sergipe, on the monthly and annual scales, between 1998 and 2013. The point values estimated by the TRMM were compared with the precipitation data obtained in 13 pluviometric stations of the National Water Agency (ANA). The statistical indications considered were the coefficient of determination (R²), mean absolute error (EMA), root of the mean square error (REQM) and Willmott’s agreement index (d). The R² values were 0.49 and 0.16 on the monthly and annual scales, respectively. For the monthly time scale, the best estimates of the TRMM product were found in the semi-arid region of the state of Sergipe, with values of R², EMA, REQM and d equal to 0.54, 27.18 mm and 38.71 mm and 0.83, respectively. Keywords: 3B43-TRMM, climatology; hydrology; rain.